FLUID-TO-FLUID AND FLUID-TO-ROCK INTERACTION ON SOPHOROLIPIDS BIOSURFACTANT FOR ENHANCED OIL RECOVERY: A LITERATURE REVIEW - Taufan Marhaendrajana; Indah Widiyaningsih; Ivan Kurnia; Harry Budiharjo Sulistyarso (Testing Center for Oil and Gas LEMIGAS, 2025)
The promising glycolipids produced by non-pathogenic yeast as biosurfactants are called sophorolipids. Their advantages over chemical surfactants are smaller environmental impact, lower toxicity, and biodegradable. They can reduce interfacial tension (IFT), form microemulsions, and alter wettability in enhanced oil recovery applications. The potential as biosurfactants is due to the resistance to high salinity and high temperature in reservoir conditions.Laboratory experiments for enhanced oil recovery (EOR) applications require to test fluid-to-fluid and fluid-to-rock interactions in the complex crude oil–rock–brine (CORB) system. This review discusses the sophorolipids mechanisms of fluid-to-fluid and fluid-to-rock interactions.Sophorolipids’ potential in EOR processes can be determined from core flooding experiments, in which some researches reported the incremental oil recovery up to obtained up to 20%. The review and discussion in this article are intended to have a broad impact on science and the petroleum industry, particularly in EOR applications.